Orbital Osteomas: Report of 3 Rapidly Progressive Cases in Adolescents and Systematic Literature Review. Issue 2 (18th June 2020) - Tooley, Andrea A.; Paulose, Sefy A.; Tran, Ann Q.; Godfrey, Kyle J.; Kazim, Michael
Abstract : Purpose: The purpose of this study was to describe the clinical characteristics, management, and outcomes of orbital osteomas in the pediatric age group, and compare these to osteomas managed in the adult population. Methods: A retrospective review of 3 cases of rapidly progressive orbital osteomas in young patients was performed. In addition, a systematic review of the literature following Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines was conducted to describe the clinical characteristics, management, and outcomes of orbital osteomas in the pediatric age group. The PubMed/MEDLINE database was searched in December 2019 for studies reporting data on patients with orbital osteomas. Results: Fifty-nine patients were included in this pediatric review, 39 male patients (68%), 18 female patients (32%), and 2 cases with unreported genders. Average age was 15.9 years with a range of 4–21 years. Average osteoma size measured 30.7 mm with a range of 9–60 mm. Adult osteoma size for comparison was smaller than 10 mm in majority of cases. The most common location of pediatric osteomas was the ethmoid sinus. The frontal sinus was the most common location in adult patients. Ninety-seven percent of reported pediatric cases required surgical intervention, compared with only 6.5% in adults. Conclusions: Orbital osteomas in younger patients are larger when identified, grow faster, are more likely to be symptomatic, and more likely to require surgical intervention compared with those identified in older patients. We recommend close monitoring of osteomas identified in young patients as well as counseling regarding the potential need for future resection. Abstract : Orbital osteomas are characteristically benign, indolent tumors in adults. We report 3 cases of rapidly progressive tumors in young patients and perform a systematic review detailing clinical characteristics and surgical outcomes of pediatric orbital osteomas.